State Regulation and Hospital Costs - Antel, John J.; Ohsfeldt, Robert L.; Becker, Edmund R. (The Review of Economics and Statistics, 1995)
The effects of various regulations on hospital costs are estimated using a two decade long panel data set which spans the initiation, and in some instances the repeal, of various forms of hospital regulation. The long panel fosters two improvements over previous research. First, as state hospital cost levels may affect states' incentive to regulate, fixed effect estimators alleviate omitted variable bias derived from the states' regulatory discretion. Second, the long panel permits the estimation of many different regulatory program effects, but also facilitates the analysis of potential regulatory program interaction. The empirical results suggest that previous studies have exaggerated regulatory cost savings: although some interaction effects are indicated, hospital costs appear unresponsive to most regulatory programs. Copyright 1995 by MIT Press.